Investigation of the red-shift of the emission of microwave solvothermally-grown europium doped calcium sulphide crystals - 董晓菲 陆启飞 卢志娟 毛智勇 王达健 (Journal of rare earths, 2014)
A distinct red-shift to 660 nm-featured longer wavelength of europium doped calcium sulphide nanocrystals was observed in a microwave （MW）-assisted solvothermal synthesis procedure. This red-shift was probably due to a combined effect from Mg^2＋ codoping and strain accumulation at grain boundaries. The latter originated from the formation of small grains with an average size of around 200 nm in micrometer sized crystals upon Mg^2＋ codoping. In particular, MW electromagnetic field suppressed grain growth and enabled a reconstruction of atoms at the inner grain boundary at which the field strength was intensified around rare earth ions in host lattices. This MW synthesis route provided an option to prepare luminescent crystals with the desired blue-excitable longer wavelength emission.